185k views
5 votes
Rewrite the function by completing the square.h(x) = x^2 + 3x – 18

1 Answer

4 votes

The function is:


h(x)=x^2+3x-18

When completing the square, we take half of coefficient of 3, square it up and add it to the constant and rearrange. THe process shown below:


\begin{gathered} h(x)=x^2+3x-18 \\ h(x)=(x+(3)/(2))^2-18-((3)/(2))^2 \\ h(x)=(x+(3)/(2))^2-18-(9)/(4) \\ h(x)=(x+(3)/(2))^2-(81)/(4) \end{gathered}

So, this is the form after completing the square.

User Wvdz
by
5.9k points